Eksistensi dan Kepercayaan Pemerintah Terhadap LSM Lingkungan dalam Penerapan Green Politics di Indonesia - Apriyani, Sinta (Jurnal Empirika, 2024)
Political activism, which cares about the environment and is embodied in the vision, mission, and programs of government and political action, must fight for the future. The form of political concern for the environment, previously referred to as environmental policy in Indonesia, has been implemented through the submission of petitions by Indonesian environmental NGOs to pay attention to ecological aspects, lawsuits over policies, and mass mobilization actions. A survey is conducted in the study. The data used to use other data to create a form of environmental and political awareness, or what is then known as "green policy" in Indonesia, is now being used by some NGOs in Indonesia to file petitions, legal procedures on regulations, and large-scale mobilization factors to draw attention to environmental aspects. The literature was used in the study. The data comes from other documents, regulations, and books. The community and the government feel the problem of this justice, which supports what is happening on social media in Indonesia. The current reality of the "green" political narrative, which some NGOs can appreciate, is not fully understood and is on the list. The existence of green cities in Indonesia is vital and should be held accountable by the government for places in Indonesia.